Aesthetical experience as pathological discourses of abjection and melancholia in the Beksinski’ art - H.O. Verbivska (Ukrainian Cultural Studies, 2020)
This article tackles the issue of aesthetic experience from the pathologized everyday discourse viewpoint in the system of relations between I and symbolic order, where transgressed and close to symbolic death I is predominant. The stage, in which I, crossing the symbolic borders, stay readable, appears to be the process of continuous constituting the aesthetic experience and its transforming into the primordial a priori structure of everyday discourse. The problem lies deeply in the preserving of evanescent borders which are said to exist in the cultural palpability and simultaneously to be exiled from the system. The article exemplifies pathological discourses by referring to the Beksinski’ works, namely his numerous ways of articulating the ineffable. However, articulated ineffable, similarly to such culturally conditioned reactions as abjection and melancholia, declares double death of the discursive subject: the first time when the separation from primordial presymbolic world takes place and the second time during problematizing the symbolic borders and paradoxical immortalization concerning postulated frontiers. The aim of this article is to dig out kaleidoscope of images and sub-images from Beksinski’ works through the motive of crucifixion resulting in the specific value of Christ’s body and chimerical things inside the dehumanized catastrophic space. It is demonstrated how pathological discourse of melancholia could be intertwined with the discourse of abjection in the common point of transgressing the limits, making the symbolic space full of details indicating the risk of Ego being disintegrated, staying inside the transgressed limits as constituting aesthetical experience. Inexplicability of terrible post-apocalyptic world is readable via symbolic coordinates insofar as the main primal object (the body of Christ) occurs to be banished. Appearing of aesthetic experience is paralleled to the stages of psychosexual development in the existence of symbolic being where in opposition to classical freudism maternal authority is accentuated. That’s how Kristevan style of psychoanalytic ruminations looks like.